Hands-On Penetration Testing with Kali NetHunter : Spy on and protect vulnerable ecosystems using the power of Kali Linux for pentesting on the go /: Spy on and protect vulnerable ecosystems using the power of Kali Linux for pentesting on the go. (2019) - Singh, Glen D; Oriyano, Sean-Philip
No abstract available